A new multi-dimensional conceptualization of individual achievement in college - Anamaria Berea; Maksim Tsvetovat; Nathan Daun-Barnett; Mathew Greenwald; Elena Cox (Decision Analytics, 2015)
Individual achievement in college has been closely tied to dropout and graduation rates and these indices of completion have been considered the most important measures for gauging achievement in undergraduate education. In this study, we both define and examine a new concept of thriving in college. Both the literature and the data suggest that a multidimensional concept of thriving is better suited for predicting student achievement. We base our data analysis on the data we collected from a nationwide survey conducted in 2013 - 2014. The survey data show that student achievement in college does not depend solely on academic performance, and that there is no single factor that predicts thriving in college, in general, for an individual student. We show that in a heterogeneous population of students and a heterogeneous set of colleges, there is no unique pattern or factor for all students to thrive in the same college. We define and quantify the concepts of multidimensional thriving, personal traits and college ecosystems and build an algorithm that shows which is the best college ecosystem for a unique student. Furthermore, we show which traits of this individual are most responsible for the subsequent thriving in this specific college and which other traits s/he should learn or acquire in order to increase these chances of thriving.
Keywords: 330; Education analytics; Thriving; College choice